1995
DOI: 10.1016/0304-3959(95)00016-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lamotrigine in the acute and chronic hyperalgesia induced by PGE2 and in the chronic hyperalgesia in rats with streptozotocin-induced diabetes

Abstract: There is still a need for a new analgesic devoid of the side effects presented by opioids or non-steroidal anti-inflammatory drugs, for the treatment of some acute and chronic pain conditions. Lamotrigine (Lamictal1, 10-100 mg/kg), a new anticonvulsant, showed analgesic effects in the acute model of prostaglandin E2 (PGE2)-induced hyperalgesia when given orally before or after the subplantar injection of PGE2 in the rat. It also inhibited the development of sustained hyperalgesia induced by multiple subplantar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 13 publications
4
35
0
1
Order By: Relevance
“…The analgesic activity of oral lamotrigine has been demonstrated in inflammatory and neuropathic models of hyperalgesia where it restores the normal responsiveness without affecting the phasic pain response [4,5]. The same profile of effects has also been observed in acute and chronic models of pain in rats after intrathecal injection of lamotrigine [15].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The analgesic activity of oral lamotrigine has been demonstrated in inflammatory and neuropathic models of hyperalgesia where it restores the normal responsiveness without affecting the phasic pain response [4,5]. The same profile of effects has also been observed in acute and chronic models of pain in rats after intrathecal injection of lamotrigine [15].…”
Section: Discussionmentioning
confidence: 95%
“…It is thought to act primarily by stabilising the presynaptic neuronal membrane by blocking voltage-dependent Na þ channels, thereby preventing the pathological release of excitatory neurotransmitters, principally glutamate [1][2][3]. Nakamura-Craig and Follenfant [4,5] have shown that oral administration of lamotrigine produces analgesia in acute (subplantar injection of PGE 2 ) and chronic (diabetic neuropathy and loose sciatic ligation) models of hyperalgesia in rats. A pilot study with volunteers using the coldpain test indicated that a single oral dose of lamotrigine 300 mg caused a significant reduction in subjective pain (unpublished data).…”
mentioning
confidence: 99%
“…Mast cell aggregates may be found in a variety of tissues including skin, bone marrow, liver, spleen, lymph nodes and the gastrointestinal tract [1,10]. The systemic variety may present as episodic flushing, pruritis, headache, palpitations, abdominal pain and diarrhoea [1,[3][4][5]10]. Unpredictable episodes of profound hypotension are a recognised feature of the disease and are due to release of mast cell mediators including histamine [11] and prostaglandin D 2 [12].…”
Section: Case Historymentioning
confidence: 99%
“…Interestingly, clinical examination did not reveal flushing, oedema or bronchospasm. These symptoms, while common in mastocytosis [4,5], are not a universal feature of anaphylaxis [23,31], making the diagnosis particularly difficult during anaesthesia. The management of this case included rapid intervention with adrenaline, and it is doubtful whether earlier therapy with steroids and antihistamines would have altered the outcome.…”
Section: Case Historymentioning
confidence: 99%
See 1 more Smart Citation